Exploring Current Status on Prevalence of Childhood Overweight and Obesity in South India: Survey Findings - Mounika Katyayani K; Vamsi Krishna Reddy K; Vamsi Krishna P; Kanta Kumari P; Vijaya Lakshmi B (Asian Journal of Clinical Pediatrics and Neonatology, 2022)
Background: Measure the prevalence of overweight and obesity among 5 to 12 year olds in Guntur city’s elementary schools. Study Design: A school-focused cross-sectional study. Study Setting: All 5000 children between the ages of 5 and 12 in Guntur were tested over a course of three years. Subjects and Methods: The Anthropometric data acquired in Microsoft Excel was examined using SPSS version 13.0. Using new IAP growth charts, BMI is computed and categorized into overweight and obesity. Results: Microsoft Excel was used to compile the anthropometric data, which was then analyzed using the SPSS version 13.0. The BMI is determined using updated IAP growth charts, and children are classified as overweight or obese based on their BMI. Overweight and obesity are most common in children aged 6-7 (23.8 percent) and least common in children aged 11-12 (16.8 percent). Government school children were relatively more overweight and obese (20.8percent) than private schools (20percent). In comparison to girls (19.17 percent), the prevalence of obesity in boys is higher (21.7 percent). The prevalence is more in lower age groups (21.6percent) than that in higher (18.78percent) age groups. Conclusion: Child obesity is on the rise, emphasizing the need for a comprehensive approach to deal with it both now and in the future, according to research.